If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 9x + 4(11 + -2x) = 0 8 + 9x + (11 * 4 + -2x * 4) = 0 8 + 9x + (44 + -8x) = 0 Reorder the terms: 8 + 44 + 9x + -8x = 0 Combine like terms: 8 + 44 = 52 52 + 9x + -8x = 0 Combine like terms: 9x + -8x = 1x 52 + 1x = 0 Solving 52 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-52' to each side of the equation. 52 + -52 + 1x = 0 + -52 Combine like terms: 52 + -52 = 0 0 + 1x = 0 + -52 1x = 0 + -52 Combine like terms: 0 + -52 = -52 1x = -52 Divide each side by '1'. x = -52 Simplifying x = -52
| 4x^4-324=0 | | (5x-6x^3+2x^4)-(9x^3+4x^4-7)= | | -2p-2(3-4p)=2(p-2)-30 | | -6+3(6-8n)=6(-7n-4) | | 2x=3+4 | | 4a+5=26-3a | | 6x+50+4x+80=180 | | 7(9+k)=98 | | -25.349(-1.369)= | | -10k-3+2(5+6k)=0 | | 9n-2=2n+5 | | -4.6r=0.2 | | 3(l)+l+2(w)=400 | | 4(8+3n)+4n=4(5n-3) | | 50+2x=1000+3 | | -8n+20=-8n-20 | | -2=4(s+8)-3a | | 3(L)+L+L+L=400 | | -2=23x-25 | | -6x+4(-2x+8)=130 | | -(c-1)=8 | | 5x-11-x=21 | | 2x*57=60x+1188 | | -2(3-2b)-3(1-b)=40 | | 1-4p-3/4= | | 3L+w=400 | | -2(3-2b)-3(1-b)=49 | | a(3x-8)= | | 4x+2(x-6)=8x+2 | | -5(4+4x)=-140 | | 9x^5-12x^4-21x^3=0 | | 2x+134=180 |